2020
DOI: 10.3390/polym12081846
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of PLLA Ductility by Blending with PVDF: Localization of Compatibilizers at Interface and Its Glycidyl Methacrylate Content Dependency

Abstract: In this work, the localization of reactive compatibilizer (RC, containing poly(methyl methacrylate) (PMMA) backbone with randomly distributed glycidyl methacrylate (GMA) on it) at the polyvinylidene fluoride/poly(l-lactic acid) (PVDF/PLLA) interface has been manipulated by means of GMA contents. At the very beginning of mixing, RC tends to stay in the PVDF phase due to the miscibility between PVDF and PMMA. Upon further shearing, more and more PLLA chains have been grafted on PMMA backbone, producing PLLA–g–PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The two each other shifted T g s of polymer blends indicate the molecular chain interpenetrating at the interface 40 . Moreover, the half‐peak‐width of SEBS‐MAH and TPAS increased in PP/TPAS/SEBS‐MAH (70/15/15) blend compared to PP/SEBS‐MAH (70/30) and PP/TPAS (70/30) blend, suggesting that SEBS‐MAH and TPAS in PP/TPAS/SEBS‐MAH (70/15/15) blend exhibited different relaxation behaviors relative to the SEBS‐MAH and TPAS in PP binary blends 41 . The evolution of the half‐peak‐width can be attributed to the influence of the esterification reaction between SEBS‐MAH and TPAS.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The two each other shifted T g s of polymer blends indicate the molecular chain interpenetrating at the interface 40 . Moreover, the half‐peak‐width of SEBS‐MAH and TPAS increased in PP/TPAS/SEBS‐MAH (70/15/15) blend compared to PP/SEBS‐MAH (70/30) and PP/TPAS (70/30) blend, suggesting that SEBS‐MAH and TPAS in PP/TPAS/SEBS‐MAH (70/15/15) blend exhibited different relaxation behaviors relative to the SEBS‐MAH and TPAS in PP binary blends 41 . The evolution of the half‐peak‐width can be attributed to the influence of the esterification reaction between SEBS‐MAH and TPAS.…”
Section: Resultsmentioning
confidence: 98%
“…The DMA data of T g and halfpeak-width for some given PP blends are listed in Table 2, it is obvious the peaks attributed to SEBS-MAH, TPAS PP/TPAS/SEBS-MAH (70/15/15) blend exhibited different relaxation behaviors relative to the SEBS-MAH and TPAS in PP binary blends. 41 The evolution of the halfpeak-width can be attributed to the influence of the esterification reaction between SEBS-MAH and TPAS. These results confirmed that the compatibility between PP and TPAS was improved resulting from the esterification reaction between SEBS-MAH and TPAS.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…Moreover, the half‐peak‐width of PBAT and PLA increased in PLA/PBAT/MAM (80/10/10) blend comparing to PLA/PBAT (80/20) blend, suggesting that PBAT and PLA in PLA/PBAT/MAM (80/10/10) blend exhibited different relaxation behaviors relative to the PBAT and PLA in PLA/PBAT blends. [ 41 ] The evolution of the half‐peak‐width can be attributed to influence of the molecular chain interpenetrating between PBAT and MAM and PLA and MAM. These results confirmed that the compatibility between PLA and PBAT was improved resulting from the addition of MAM.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the presence of hydroxyl groups plays an important role in improving the compatibility between BIIR and PLA. The improved interfacial adhesion will help the stress transfer among the phases, leading to the high flexibility of the blend ( Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%